2016
DOI: 10.1016/j.acap.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Adolescent Report of Patient-Centered Care and of Quality of Primary Care

Abstract: Objective Few studies have examined adolescent self-report of patient-centered care (PCC). We investigated whether adolescent self-report of PCC varied by patient characteristics and whether receipt of PCC is associated with measures of adolescent primary care quality. Methods We analyzed cross-sectional data from Healthy Passages, a population-based survey with 4,105 tenth-graders and their parents. Adolescent report of PCC was derived from four items. Adolescent primary care quality was assessed by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 67 publications
2
11
0
3
Order By: Relevance
“…In addition, it may be possible to identify psychological and social factors influencing health-risk behaviors such as smoking and alcohol consumption [29,30,31,32]. Several studies revealed that the assessment of psychological and social issues during medical consultations is related to positive experience, disclosure, and engagement with care of adolescents and young adults [33,34,35], supporting the current results. Furthermore, the present findings are consistent with a review conducted by Ambresin et al [36] Table 4).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, it may be possible to identify psychological and social factors influencing health-risk behaviors such as smoking and alcohol consumption [29,30,31,32]. Several studies revealed that the assessment of psychological and social issues during medical consultations is related to positive experience, disclosure, and engagement with care of adolescents and young adults [33,34,35], supporting the current results. Furthermore, the present findings are consistent with a review conducted by Ambresin et al [36] Table 4).…”
Section: Discussionsupporting
confidence: 78%
“…The response rate was very high (over 90%) in contrast to some school-based surveys in other countries which report much lower rates of parental agreement to participate. (32) Another strength is that the questions include a range of important health complaints among this age group and key aspects of GP consultations that have been highlighted in previous literature. (33) However, other data which have been previously studied and would have been of interest were not included.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As sugestões que emergem dos dados para mudanças futuras assentam em alguns dos critérios de qualidade definidos para os serviços de saúde amigos dos adolescentes 16,17,27 , como o serem mais acessíveis com horários, locais e funcionamento, que permitam o fácil acesso, apropriados ao disponibilizarem serviços adequados às suas necessidades, e aceitáveis quando oferecem cuidados que respondem às expetativas dos adolescentes motivando a procura 16,17,20 . Estes requisitos têm subjacente a filosofia dos cuidados centrados na pessoa do adolescente, uma medida da qualidade de cuidados em saúde 18,19 .…”
Section: Discussionunclassified
“…Ou seja, serviços que cumpram critérios de qualidade, atendendo a um conjunto de características e condições: sejam acessíveis, aceitáveis, apropriados, efetivos e que respeitem a equidade 17 . Neste contexto, cuidados de saúde de qualidade correspondem a cuidados centrados na pessoa do adolescente, ou seja, que respeitam e respondem às preferências, necessidades e valores dos adolescentes 18 .…”
Section: Preferências Dos Adolescentes Sobre Os Cuidados De Saúdeunclassified